How does mindfulness affect media employees’ creative engagement? The chain-mediation model of institutional pressures and career adaptability - Wu, Meiying; Gao, Yongxuan (Frontiers in Psychology, 2025)
BackgroundArtificial intelligence is reshaping media production, forcing professionals to confront stringent institutional pressures and rising innovation demands. Although employee mindfulness is a critical psychological resource, its mechanism for fostering creative engagement under high constraints remains unclear.ObjectiveThis study examines how employee mindfulness influences creative engagement through a chain-mediation model of institutional pressures and career adaptability among Chinese media professionals.MethodsData from 804 media professionals were analyzed using hierarchical regression and PROCESS Macro (Model 6) to test direct and indirect effects, controlling for demographic variables.Results(1) Employee mindfulness, institutional pressures, and career adaptability each have significant direct predictive effects on media professionals’ creative engagement; (2) Institutional pressures and career adaptability play a chain mediating role in the relationship between employee mindfulness and creative engagement, with this mediating effect involving three pathways: employee mindfulness → institutional pressures → creative engagement (indirect effect = 0.094, 95% CI = [0.060, 0.134], accounting for 25.54% of the total effect); employee mindfulness → career adaptability → creative engagement (indirect effect = 0.069, 95% CI = [0.043, 0.098], accounting for 18.75% of the total effect); employee mindfulness → institutional pressures → career adaptability → creative engagement (indirect effect = 0.042, 95% CI = [0.027, 0.060], accounting for 11.41% of the total effect).ConclusionMindfulness promotes creative engagement by reducing institutional pressures and enhancing career adaptability, revealing a “cognitive restructuring-capability enhancement” mechanism. Findings offer theoretical and practical insights for balancing compliance and innovation in media organizations.